Dimensions of Social Justice Leadership: A Critical Review of Actions, Challenges, Dilemmas, and Opportunities for the Inclusion of Students with Disabilities in U.S. Schools - David DeMatthews (Universidad Autónoma de Madrid, 2014)
Empirical research has described how school leaders with social justice orientations investigate, understand, and address issues related to marginalization. These studies detail many of the heroic efforts of principals and their dedication, persistence, and skill. Theoretical and empirical writings have often presented social justice leadership as a "cure-all" to inequities rather than politically situated leadership orientation that in its practice is dilemma-laden. This article draws upon previous research on effective leadership as well as highlighting key aspects related to special educational policy in U.S. public schools to cultivate a more in-depth understanding of the practice of social justice leadership for inclusion. This analysis is presented to prompt a more in-depth and practice-oriented discussion, analysis, and understanding of the challenges associated with social justice leadership. Recommendations for future research and a more community-oriented and activist approach to social justice leadership are presented and justified at the conclusion of the article. Keywords: Social justice, Leadership, Educational policy, Special education.   La investigación empírica ha descrito cómo los líderes escolares con orientaciones hacia la justicia social investigan, comprenden y abordan las cuestiones relacionadas con la marginación. Estos estudios muestran en detalle muchos de los esfuerzos heroicos de los directores, su dedicación, persistencia y habilidad. Escritos de carácter teórico y empírico que, a menudo, presentan el liderazgo para la justicia social como algo capaz de "curar" las desigualdades, en vez de mostrar el liderazgo como una práctica políticamente orientada y cargada de dilemas. Este artículo se basa en investigaciones previas sobre el liderazgo eficaz, y destaca aspectos clave relacionados con la política educativa de las escuelas públicas que fomentan una comprensión más profunda del liderazgo para la justicia social para la inclusión. Este análisis se presenta para provocar una mayor profundidad y discusión orientada a la práctica, el análisis y la comprensión de los retos asociados con el liderazgo para la justicia social. Se presentan y justifican en las conclusiones del artículo algunas recomendaciones para futuras investigaciones y un enfoque más orientado a la comunidad y activista con el liderazgo para la justicia social. Descriptores: Justicia social, Liderazgo, Política educativa, Educación especial.   A pesquisa empírica descreveu como líderes para a da justiça social investigam, compreender e resolver problemas de marginalização. Esses estudos mostram em detalhes muitos dos esforços heroicos dos líderes, a dedicação, a persistência e habilidade. Escritos de caráter teórico e empírico, muitas vezes exibem líderes capazes de "curar" desigualdades, em vez de mostrar liderança como uma prática politicamente orientada e cheio de dilemas. Este artigo é baseado em pesquisas anteriores sobre a liderança eficaz, e destaca os aspectos fundamentais da política de educação nas escolas públicas que promovam uma compreensão mais profunda da liderança para a justiça social para a inclusão. Essa análise é apresentada para causar maior profundidade e discussão orientada para a prática, análise e compreensão dos desafios associados com a liderança para a justiça social. Nós apresentamos e justificam as conclusões do artigo algumas recomendações para futuras pesquisas e uma liderança mais voltado para a comunidade e ativista para abordagem de justiça social. Palavras-chave: Justiça social, Liderança, Política de educação, Educação especial.